Chironomidae (Diptera-Insecta) Fauna of TMI 12 Pond (Elazig-Turkey) - Arslan, Serkan; Saler, Serap (Medwell Online, 2010)
Bottom samples were collected monthly between September 2005 and November 2006 from 3 stations in order to determine Chironomidae larva and their seasonal distributions of TMI 12 Pond. During the study period 14 species belonging to 2 subfamily of Chironomidae were recorded. Chironomus plumosus was determined as the dominant species. Chironomus plumosus, Chironomus thummi, Chironomus anthracinus and Chironomus tentans were present in all stations. The most numbers of larvae were recorded in winter, the lease were recorded in spring months. Also spring was recorded as the poorest season as to Shannon-Wiener species diversity index values. The other seasons index results were showed similarities with each other.
Keywords: Chironomidae larvae; seasonal distribution; biological diversity index; TMI 12 Pond; spring; Turkey